Syntactic Structure of Nominal Sentences in Modern Arabic - Haq, Aidilla Daffa El; Mimantasyah, Virza; Putri, Rahma Dwi; Nasution, Sahkholid (Lembaga Riset Mutiara Akbar, 2025)
This study aims to examine the syntactic structure of nominal sentences in Modern Standard Arabic (MSA) by emphasizing the constituent components, structural patterns, and functional relationships between mubtada? (subject) and khabar (predicate) in various contexts of language use. This study uses a descriptive-qualitative approach with data sources in the form of contemporary Arabic texts, including scientific journal articles, academic texts, and Arabic-language mass media. The data were analyzed using content analysis techniques by identifying variations in the structure of the number of ismiyyah, types of khabar, element placement patterns, and accompanying pragmatic functions. The results show that although the basic structure of nominal sentences in MSA still maintains the traditional mubtada?–khabar pattern, its realization in contemporary discourse shows high flexibility. Variations in nominal structures are influenced by genre factors, information focus, and the speaker's communicative purpose. Nominal sentences in academic texts tend to be definitional and stable, while those in mass media are concise, informative, and persuasive. This study concludes that the nominal sentence structure in Modern Arabic not only represents grammatical rules, but also functions as a semantic and pragmatic strategy in discourse management.